(untitled) (International Journal of Studies in Nursing, 2018)
Postoperative breathing exercises are widely important for patient to prevent postoperative respiratory complications. Breathing exercises had a highly positive effect on improving quality of recovery among post-operative patients. This study aimed to assess the effect of breathing exercises on quality of recovery among post-operative patients. Setting at Zagazig University Hospitals. Material and Method: a quasi-experimental (pre and posttest design). A purposive sample of total 258 study participants, 129 in experimental and 129 in control group based on inclusion and exclusion criteria. Data collection questionnaire were prepared with extensive review of previous literatures. Data collection through three tools includes, interviewing questionnaire sheet, postoperative quality scale and visual analogue scale of patient postoperative quality assessment scale. Breathing exercise (BE) was taught and practiced by the patients in experimental group and in control group routine postoperative care was followed. Result: postoperative quality rate was significantly different in experimental group were higher than in control group. Conclusion: post-operative breathing exercises improve postoperative quality.